Core Stabilization Exercise on the Lumbar Lordosis and Pelvic Inclination Among Chronic Nonspecific Low Back Pain Patients - Leo R athinaraj Antony Soundararajan (Journal of Spine Practice)
Introduction: Chronic low back pain (CLBP) is one of the most common musculoskeletal disorders and it is documented that >90% of the cases have no defined cause for pain, called nonspecific low back pain (NSLBP). Alteration in the joint position, abnormal posture, and impaired muscle recruitment may result in recurrent CLBP. Lumbar lordosis (LL) provides strength against the compressive forces of gravity and it also protects the posterior spinal ligament and acts as a shock absorber for vertical forces. Increased LL is considered as a reason for radiculopathy, facet pain, and postural pain. Spinal posture and pelvic position were analyzed and documented as altered in CLBP patients. Anatomically, the anterior and posterior tilt of the back and pelvis by the force of different muscles can alter the spinal curvature. Posterior pelvic tilt in a standing position can decrease the LL. The pelvic inclination is related to the lumbar curve, and both are related to the performance and length of the back and abdominal muscles. Therefore, in this study, we aimed to evaluate the effect of core stabilization exercise on pain intensity, functional disability, LL, and pelvic inclination in NSLBP.